THE STRUGGLE BETWEEN POLITICAL AND IDEOLOGICAL OVER THE IMPLEMENTATION SHARIA-NUANCED REGIONAL REGULATION - Musahadi Musahadi (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2020)
The positivation of Sharia (Islamic law) is an important topic that remains interesting to raise when discussing the institutionalization of Sharia in Indonesia. This topic is also a significant theme in the discussions of Islamic law in other parts of the Islamic world. How to make Islamic law as legal rules that apply nationally is one of the primary agenda. The objective is clear, that is so that Islamic law is neither merely an ideal law found in the collective awareness in the community’s belief system nor an